Money politics and the obstacles on national leadership succession - Suswantoro, Gunawan (Political Science Program, Universitas Negeri Semarang, 2021)
This paper reflects the succession of national leadership, especially at the level of regional leaders. The succession of the national leadership is currently facing various problems, including insufficient competencies, poor quality of regeneration from political parties, and the presence of many prospective leaders who suddenly enter during the election process. The problems in the regeneration of national leaders occur due to many factors. One of the most influential factors in the author's view is the rise of money politics in the Pilkada (Regional Simultaneous Election). Money politics is a severe obstacle in democratic life because it has proven successful in blocking the way for the regeneration of potential leaders—likewise, political parties are trapped in carrying candidates with